Assessing socio‐environmental suitability and social license of proposed offshore aquaculture development: A Florida case study - Amanda G. Guthrie; Nicole Barbour; Sara E. Cannon; Sara E. Marriott; Phoebe Racine; Ruth Young; Ashley Bae; Sarah E. Lester; Adriane Michaelis (Journal of the World Aquaculture Society, 2024)
Abstract Offshore aquaculture is a growing industry, but a lack of social acceptance is limiting development, including within the USA. We used the Gulf Coast of Florida, where there has been industry and government interest in development, as a case study to explore offshore aquaculture potential and methods for integrating stakeholder concerns into offshore aquaculture development. We assessed (1) social acceptance of offshore aquaculture in the Florida Gulf Coast using public comments; (2) site suitability for offshore development using social, biological, and technical data; and (3) potential impacts of offshore aquaculture on communities using socioeconomic vulnerability indices. We found that many stakeholders distrust policymakers and industry and have concerns about potential environmental impacts. We created species‐specific suitability maps for red drum (Sciaenops ocellatus) and almaco jack (Seriola rivoliana), demonstrating that large areas of the Gulf are suitable for offshore aquaculture development. We show that many coastal and fishing‐reliant communities have existing vulnerabilities that aquaculture development could affect, but the public comments did not reflect these. To gain social acceptance, industry and government agencies will need to better incorporate public feedback into planning processes in a meaningful way. Consulting local communities and adapting projects in response to their concerns can help to secure social license for offshore aquaculture.